Alelopatia da samambaia pteridium esculentum (G. Forst.) cockayne em uma floresta estacional semidecidual - Santos, Kezia Catein dos (2022)
The impact of clearings dominated by Pteridium esculentum (G. forest.) Cockayne in delaying ecological restoration is a worldwide concern because areas invaded by this fern occur in thousands of square kilometers that were previously forested. In conservation units (UCs), such as the National Forest of Pacotuba, where there is an invaded fragment, restoration is of great importance because even small fragments in UCs can harbor high biological diversity, requiring measures to increase the management for the conservation of these species. areas. Therefore, the objective of this work was to evaluate the soil seed bank in the area invaded by P. esculentum, as well as the transposition of the forest seed bank in the presence or absence of fronds of the species. In addition, to analyze whether the fern has an allelopathic effect on native species. The following hypotheses were tested: (i) P. esculentum fronds negatively influence the germination of species from the soil seed bank in the forest nursery; (ii) allelochemicals present in dry fern fronds reduce the richness and number of individuals that germinate in the field; and (iii) higher numbers of Handroanthus heptaphyllus Mattos seeds germinate when irrigated with less concentrated P. esculentum (G. forest.) Cockayne extracts (iv). Experiments were carried out comprising the germination of the seed bank from the soil in the forest nursery and the transposition of the seed bank from the interior of the forest to the area, in 20 plots installed in open gaps. For the allelopathic tests in the laboratory, aqueous extracts of the species were used on H. heptaphyllus seeds. The choice of the species was due to the high availability of viable seeds in the forest nursery. As a result of the germination of the seed bank in the nursery, no individuals of P. esculentum were found, the bank was composed mainly by species of the families Asteraceae and Melastomataceae. The transposition of the seed bank to the invaded area resulted in the germination and growth of a single species, Trema micrantha, which occupied practically all the plots, including the control treatment plots, indicating that the seeds were not taken only with the transposition technique. The average time of germination and the growth of the aerial portion of the individuals of H. heptaphyllus were influenced by the extracts of P. esculentum, however it is necessary that more studies are carried out in order to understand the action of allelochemicals on the germination of seeds of species native.